Photonic crystal fiber based dual-wavelength Q-switched fiber laser using graphene oxide as a saturable absorber - Ahmad, Harith; Soltanian, M.R.K.; Pua, C.H.; Alimadad, M.; Harun, Sulaiman Wadi (Optical Society of America, 2014)
A Q-switched dual-wavelength fiber laser with narrow channel spacing is proposed and demonstrated. The fiber laser is built around a 3 m long erbium doped fiber as the gain medium and a 10 cm long photonic crystal fiber (PCF) as the element used to generate the dual-wavelength output. The PCF has a solid core approximately 4.37 μm in diameter and is surrounded by microscopic air-holes with a diameter of about 5.06 μm each as well as a zero-dispersion wavelength of about 980 nm. A graphene oxide based saturable absorber is used to generate the desired pulsed output. At the maximum pump power of 72 mW the laser is capable of generating pulses with a repetition rate and pulse-width of 31.0 kHz and 7.0 μs, respectively, as well as an average output power and pulse energy of 0.086 mW and 2.8 nJ, respectively. The proposed fiber laser has substantial potential for use in applications that require longer duration pulsed outputs such as in range finding and terahertz radiation generation.